Synthesis, characterization and photoluminescence properties of Eu3+ doped columbite CdNb2O6 - BAŞAK, ALİ SADİ; EKMEKÇİ, METE KAAN (ELSEVIER GMBH, 2016)
Pure and Eu3+-doped CdNb2O6 powders have been prepared by a molten salt synthesis method using Li2SO4/Na2SO4 salt mixture as a flux at relatively low temperatures as compared to solid state reaction. X-ray diffraction patterns of pure CdNb2O6 samples indicated orthorhombic single phase. Photoluminescence investigations of CdNb2O6 samples showed a strong blue emission band centered at 460 nm. For Eu-doped CdNb2O6 samples, the luminescence of Eu3+ was observed with the host red emission varying with the Eu-doping concentrations. This PL characteristic of the doped samples may be attributed to the energy transfer between Eu3+ and niobate groups (NbO6). (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Molten salt process; Luminescence; Columbite cadmium niobate; MOLTEN-SALT SYNTHESIS; LUMINESCENT PROPERTIES; ENERGY-TRANSFER; NIOBATES; LINBO3